Evaluation of the effect of fungicides on the development of two species of Trichoderma (Fungi: Ascomycota: Hypocreaceae) used in the biocontrol of cacao pathogenic fungi - Guerrero, Raquel (2012)
The presence of the fungal pathogens Moniliophthora perniciosa (witches’ broom) and M. roreri (moniliasis) on cacao crops in Ecuador destroys large percentages of the production. There are various methods currently used to reduce the impact of these pathogens, including cultural practices, chemical control and genetic resistance. Additionally, several research centers are evaluating biological control measures with good prospects for Integrated Crop Management (ICM). For integrated management, in which the application of chemical fungicides is combined with biological control methods, the biocontrol agents should be resistant to the chemical fungicide. This investigation evaluated two biological control agents, Trichoderma koningiopsis and T. stromaticum that have the potential to be included into integrated control management programs for cacao. The bioontrol agents were tested with two commonly-used cacao fungicides, copper oxide and azoxystrobin. The results show that while T. koningiopsis grew in all the treatments, it grew considerably more when used in conjunction with the fungicide azoxystrobin than with copper oxide. Trichoderma stromaticum only grew with azoxystrobin. These results demonstrate the possibilities for future use of these two biocontrol agents in integrated management strategies for cacao crops.